An investigation on bond between FRP stay-in-place formwork and concrete. (15th June 2016) - Goyal, Reema; Mukherjee, Abhijit; Goyal, Shweta
Highlights: Experiments on bond between FRP stay-in-place formwork and concrete are conducted. Effect of adhesive type has been explored using both adhesive bonding and aggregate bonding. The interfacial strength has been estimated using a finite element model. Failure mode and ultimate strength depends upon the type of the adhesive. At the limiting state the failure mode shifted from the interfacial to concrete failure. Abstract: FRP stay-in-place (SIP) formworks are designed to act as a support for casting concrete and as a tension reinforcement when the concrete is cured. For composite action between the formwork and concrete, proper bond between them is essential. This investigation focuses on the role of adhesives for the bond development. Two different bond mechanisms, aggregate bonding and adhesive bond, are investigated using three different adhesives. A novel experimental set up is prepared to evaluate the bond. The load capacities and failure modes were examined. Load–deflection, load-slip and load-strain curves have been plotted to evaluate the bond mechanisms. A finite element model is developed that is able to accurately predict the ultimate pullout load and load-slip relationships. The results show that the types of resins have a great impact on the bond. It is recommended to use the wet-bond technique with special adhesives.